2022
DOI: 10.3390/ijms23042037
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Cryogels as Promising Materials for Biomedical Applications

Abstract: The availability, biocompatibility, non-toxicity, and ease of chemical modification make cellulose a promising natural polymer for the production of biomedical materials. Cryogelation is a relatively new and straightforward technique for producing porous light and super-macroporous cellulose materials. The production stages include dissolution of cellulose in an appropriate solvent, regeneration (coagulation) from the solution, removal of the excessive solvent, and then freezing. Subsequent freeze-drying prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 117 publications
1
45
1
Order By: Relevance
“…To improve their mechanical properties, chemical crosslinking with functionalized molecules was introduced. It has been revealed that different approaches of drying and fabrication such as vacuum drying, freeze–thawing and freeze drying can provide dissimilar biomaterials for different biomedical applications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve their mechanical properties, chemical crosslinking with functionalized molecules was introduced. It has been revealed that different approaches of drying and fabrication such as vacuum drying, freeze–thawing and freeze drying can provide dissimilar biomaterials for different biomedical applications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of different factors affect the structure of cryogels [10]. The freezing temperature affects the cryogel's structure.…”
Section: Introductionmentioning
confidence: 99%
“…The freeze-drying process will generate pores and a complex three-dimensional structure with similar properties to natural soft tissues. The origin of the polymer, dissolution parameters, and type of solvent, as well as the temperature and freezing rate, can affect the formation of cryogels [ 39 ].…”
Section: Natural Hydrogelsmentioning
confidence: 99%